THE INFLUENCE OF CORPORATE SOCIAL RESPONSIBILITY AND MANAGEMENT COMPENSATION ON COMPANY PERFORMANCE WITH INDEPENDENT COMMISSIONERS AS MODERATING VARIABLES - Loveana Syaifora; Yolanda Pratami; Saiful Anuar (International Journal of Social Science, 2022)
Company performance is a measure of management's success in running the company. This study aims to empirically examine the effect of Corporate Social Responsibility and management compensation on company performance with independent commissioners as moderating variables. This study uses quantitative methods with multiple regression analysis techniques. The population in this study was all banking companies listed on the Indonesia Stock Exchange in 2018-2020 with a total sample of 78 companies. The results of the tests that have been carried out show that Corporate Social Responsibility has a negative effect on company performance. Management compensation has an effect on company performance. Furthermore, Corporate Social Responsibility has an effect on company performance with independent commissioners as a moderating variable. Finally, management compensation has an effect on company performance with independent commissioners as a moderating variable.